The Effects of Sport Life Skills and Life Skills Transfer on Student-Athletes and Coaches: An Application of Actor-Partner Interdependence Model (APIM) - Chang-Yong Jang; Hongsun Song (Korea Institute of Sport Science, 2022)
PURPOSE This study examined the effect of sports life skills and life skills transfer of student-athletes and coaches, applying Actor-Partner Interdependence Model (APIM). METHODS Korean student-athletes and coaches from middle and high school sports teams participated in this study. There were 300 student-athletes (Mage=15.44, SD=1.64; male=218, female=82), with an average of 5.46 (SD=2.40) years of athletic career. Meanwhile, 33 coaches were (Mage=39.70, SD=8.36; male=26, female=7), with an average of 13.52 years of coaching career (SD=10.01). Measures included the Life Skills Scale for Student-Athletes (LSSSA; Jang et al., 2020) and Korean Life Skills Transfer Survey (KLSTS; Lim et al., 2018). Descriptive analysis, correlation, and APIM were undertaken by using the SPSS and AMOS programs. RESULTS First, the correlation between athletes' and coaches' life skills was not significant. Second, athletes' life skills significantly affected their life skills transfer, similar to coaches' life skills significantly affecting their life skills transfer. Fourth, coaches' life skills did not significantly influence athletes' life skills transfer, and the converse was not true either. CONCLUSIONS This study verified the effect of life skills development for two groups of athletes and coaches, on transfer in sports, and attempted statistical verification of whether it affects sports life skills and transfer between athletes and coaches. Although no statistically significant results were found in the partner effect, it is meaningful in that, it provided important implications for conducting a follow-up study on the relationship between athletes and coaches. In other words, it is expected to be a cornerstone for research on building a new model, along with investigating the interactive relations between athletes and coaches on life skills in the sports field.